2015
DOI: 10.1002/cpe.3572
|View full text |Cite
|
Sign up to set email alerts
|

Interest prediction in social networks based on Markov chain modeling on clustered users

Abstract: SUMMARYEffective user interest prediction is significant for service providers in a set of application scenarios such as user behavior analysis and resource recommendation. However, existing approaches are either incomplete or proprietary. In this paper, user interest prediction based on the Markov chain modeling on clustered users is proposed with the following procedure: collect dataset from 4613 users and more than 16 million messages from Sina Weibo; obtain each user's interest eigenvalue sequence and esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…With respect to the prediction model, machine learning methods were widely used in this field [31][32][33]. It was confirmed that the boosting and ensemble algorithms have superior performance in prediction field [34], but large dataset was required for those model learning, and it was not match to this work due to the collected dataset was insufficient. It is worth noting that the dataset in this work is high dimensional which was composed of electricity consumption and 40 climate factors, and SVR was recommended to perform the small-scale and high dimensional dataset.…”
Section: Related Workmentioning
confidence: 84%
“…With respect to the prediction model, machine learning methods were widely used in this field [31][32][33]. It was confirmed that the boosting and ensemble algorithms have superior performance in prediction field [34], but large dataset was required for those model learning, and it was not match to this work due to the collected dataset was insufficient. It is worth noting that the dataset in this work is high dimensional which was composed of electricity consumption and 40 climate factors, and SVR was recommended to perform the small-scale and high dimensional dataset.…”
Section: Related Workmentioning
confidence: 84%
“…Initialization phase: Define a three-dimensional array S [C][N] [2] to store the vertices in each segmented subgraph and whether the vertex is accessed. Initially, the vertex's access flag is set to 0, and if it is accessed, it is modified to 1.…”
Section: Minimum Degree Vertex Partitioning Algorithmmentioning
confidence: 99%
“…Graph is a ubiquitous data structure that is widely used in various fields. The keyword query based on RDF graph structure is currently a research hotspot; it allows users to obtain efficient query results without any complex structure query language, and using graphs to represent RDF data can not only maintain the correlation information between the data but also cannot lose semantic information 1–4 . Therefore, the query processing of RDF data is usually transformed into a graph matching problem, that is, positioning the Steiner tree containing keywords on the RDF data graph 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to memoryless properties, Markovian model is a widely used tool for the analysis of large‐scale systems . Markovian model has already been applied to characterize user mobility in simulation of large‐scale scenarios with traditional circle coverage base stations .…”
Section: Related Workmentioning
confidence: 99%